Implementasi Struktur Tiga Babak dalam Penulisan Naskah Video Feature “Kopi Semangka” - Mutiara Amisyah; Encang Saepudin; Nurmaya Prahatmaja (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The growth of the specialty coffee industry in Indonesia has driven various post-harvest processing innovations, one of which is coffee with a flavor character resembling watermelon (watermelon notes) produced by Fugol Cafe & Roastery through an anaerobic natural process without artificial flavoring. This phenomenon has not been widely discussed in audiovisual form, prompting the author to create a feature video titled